Phytochemical and In-vitro Antioxidant Activity of Guiera senegalensis (Combretaceae) Leaf Extracts - Hayatou, Mas’-ûd; Herve, Bayaga; Abongwa, Lem Edith; Tembe, Estella Achick; Borgia, Njinkio Nono; Fokunang, Charles Ntungwen (Journal of Advances in Medical and Pharmaceutical Sciences, 2024)
Guiera senegalensis is a plant of the Combretaceae family, found in West Africa and Central Africa. It has many properties such as antibacterial, antifungal, anticancer, antioxidants, which are the subject of this study. The objective of this study was to realize a qualitative and quantitative phytochemical screening, evaluation of the antioxidant activity of the plant leaf extracts. Plant extractions was done in accordance with the methods described by Fonmboh and collaborators on the leaves of the plant; a qualitative phytochemical screening according to the methods described by Shaik and al quantitative phytochemical screening consisting of colorimetric dosage and finally the antioxidant activity was explored in-vitro by the Folin-Ciocalteu method and by the phosphomolybdenum method. This study revealed the presence of primary metabolites such as carbohydrates and proteins but also secondary metabolites such as alkaloids, flavonoids and coumarins. Quantification analysis demonstrated a significant concentration of these metabolites depending on the extract. Carbohydrates, proteins and polyphenols had a higher concentration in the hydro-ehtanolic extract with concentrations of 45,38 ± 1,88, 1172,31 ± 17,59, 310,27 ± 11,83 µg/ml respectively. Flavonoids, flavonols and alkaloids in the Aqueous maceration extract with concentrations of 145,84 ± 8,34, 169,52 ± 10,13, 320,56 ± 67,52 µg/ml. and Tannins in decoction extract with a concentration of 338,55 ± 12,25 µg/ml. The in-vitro antioxidant activity demonstrated an inhibition percentage of the order of 70.96 ± 0.58% in the extract obtained by hydro-ethanolic maceration. This study confirms the use of the plant in category 1 traditional medicine, and results show a promising potential for developing a category 2 phytomedicine. Future studies should explore the use of phytochemical compounds involved in this antioxidant activity as well as its mechanism.